A simple generalized equation of state (2005)
A pressure perturbation technique based on a simple adaptation of the Weirtheim's first order thermodynamic perturbation theory has been developed and used to formulate a generalized equation of state. The practical equation formulated was applied to pure fluids, binary systems and real samples of Niger Delta Petroleum fluids. Tuning of data is not required. The results show more accurate predictions than the commonly used SRK and PR equations. This work provides a theoretical framework for improving the accuracy of cubic equations of state. One major advantage of the generalized equation expressed in this work is the fact that it provides a theoretical framework for explaining the physical significance of the parameters in multi-parameter equations of state. Thus, in a three-parameter equation of state, while 'a' captures the attractive forces, 'b’ is the co-volume, 'c ' could represent non-physical forces. This is different from the concept of 'c' in such equations as Peng-Robinson EOS where 'c ' obviously represents an "after-the-fact" volume correction term.